Management intensive grazing - Insight Media (Firm) (New York, NY : Distributed by Insight Media ; [Lafayette, LA] : University of Louisiana at Lafayette, 2001)
This program highlights a sustainable approach to the management of pastures, demonstrating how it results in higher use rates of nutritious forage and, ultimately, lower-cost and higher-profit livestock production. It examines the dynamics of plant growth, stock density, and harvest efficiency.
DVD
No Master.
Keywords: Grazing; Range management; Sustainable agriculture